Dynamic Susceptibility of Skyrmion Clusters in Co/Pt Nanodots - Escrig-Murua, J; Tejo-Lazo, F; Casagrande-Denardin, J; Saavedra-Díaz, E (American Institute of Physics, 2020)
We study the dynamic susceptibility of skyrmion clusters in Co/Pt nanodots using micromagnetic simulations. For this, we investigate the dynamic response of the skyrmions to a small magnetic field pulse applied parallel to the dot axis. Skyrmions exhibit a main resonance peak associated with the skyrmions breathing mode, which is closely linked to the average radius of the skyrmions. Furthermore, we find that non-trivial secondary modes appear when the cluster size increases. These results can be used as a detection and characterization mechanism for skyrmion lattices in confined systems. © 2020 Author(s).